Evaluación participativa del estado de conservación y potencial de los recursos en dos comunidades de la cuenca del Nanay, Región Loreto. 2018 - Picciotti Lopez, Orestes (2024)
The theme was “Participatory evaluation of the conservation status and potential of resources in two communities of the Nanay basin, Loreto Region”. 2018. The objectives of this study are framed in knowing the methods of conservation and use of natural resources (forests) in two communities of the Nanay basin, in the Loreto region, and also learning how producers think about the maintenance and protection of forests in the region. The study was descriptive. A simple random probabilistic sampling of 48 owners (24 per community) was used. The results of the surveys were interpreted using descriptive statistics. The results were achieved; of the economic activities, carrying out hunting and fishing activities (72.9%), crafts in wood and fiber (79.2%), extraction of forest products such as aguaje, irapay leaves, native fruits such as pijuayo, ungurahui, leaves for wrapping: bijao. Currently, some forest species such as quillosisa, cumala and lupuna are conceived in the forests, and valuable commercial species such as cedar, mahogany, rosewood, lupuna, tronillo, etc. were exploited. Forest species are preserved within the forest, taking advantage of natural regeneration to market marupa and cumala seedlings. The inhabitants maintain family gardens, which constitute an activity that generates economic income with the sale of caimito (12.7%), aguaje (5.9%), pineapple (7.8%), mango (5.9%), and it also promotes the conservation of forest species such as cumala (2.8%), cedar 11.8%. Use of medicinal species such as: sacha garlic (5.9%), mallow (4.9%), holy herb (2.9%).